Interception oleh TNI Angkatan Udara Terhadap Maskapai Ethiopian Airlines di Bandar Udara Hang Nadim Batam - Hadhani, Muhammad Gading Bintang (Media Hukum Indonesia (MHI), 2025)
Aircraft interception is an action taken by a country's military aircraft to identify and escort foreign aircraft entering airspace without permission, as regulated in the 1944 Chicago Convention and Law 1/2009 on Aviation. This article discusses regulations related to interception and the actions taken by Indonesian authorities in the case of Ethiopian Airlines which was forced to land because it crossed without permission. The formulation of the problem in this article is (1) What are the regulations related to interception? and (2) What actions were taken by Indonesian authorities in relation to the above case? Using a normative legal research method with a statutory regulatory approach and a case approach, this article analyzes national and international legal regulations related to interception and their application in Indonesia. The discussion of the article shows that interception has a primary function as a law enforcement measure and assistance to aircraft experiencing technical problems, with procedures that must comply with the provisions of Annex 2 of the Chicago Convention. The Ethiopian Airlines case is a concrete example of the application of interception in Indonesia, which emphasizes the importance of airspace surveillance in maintaining national security and sovereignty.